Screening for traumatic exposure and psychological distress among war-affected adolescents in post-conflict northern Uganda. - McMullen, J; O'Callaghan, P; Richards, J; Eakin, J; Rafferty, H (2012)
BACKGROUND: The war in northern Uganda has had a debilitating effect on the mental health of children and adolescents in the population. This study measures the prevalence and considers the aetiology of psychological distress in war-affected adolescents 4 years after the end of the conflict. METHODS: This is a cross-sectional study of 205 adolescents, aged 12-19, from a boarding primary school in Gulu, northern Uganda. A war experiences checklist was developed with the assistance of local professionals. The Impact of Event Scale-Revised (IES-R) measured post-traumatic stress symptoms. Finally, the Acholi Psychosocial Assessment Instrument (APAI) was used to measure locally described mental health constructs similar to the Western concepts of depression and anxiety. RESULTS: Four years after the end of the war, 57% of the students were still found to have clinically significant levels of post-traumatic stress symptoms using a similar cut-off score to previous studies among the same population. Both components of traumatic exposure: (i) the number of types of traumatic event experienced; and (ii) whether the adolescent was abducted were significantly associated with psychological distress. There was a strong correlation between post-traumatic stress symptoms and internalising symptoms. CONCLUSION: War-affected adolescents may continue to suffer from significant psychological stress in the years following the cessation of conflict. Multiple exposure to a number of different types of traumatic event may directly increase the likelihood of psychological distress especially for those exposed to the most extreme violence. The feasibility of employing a locally developed and validated screening instrument is demonstrated. Implications for future research and intervention in post-conflict areas are considered.